Early‐onset epileptic encephalopathy and severe developmental delay in an association with de novo double mutations in NF1 and MAGEL2. Issue 1 (23rd November 2017) - Akamine, Satoshi; Sagata, Noriaki; Sakai, Yasunari; Kato, Takahiro A.; Nakahara, Takeshi; Matsushita, Yuki; Togao, Osamu; Hiwatashi, Akio; Sanefuji, Masafumi; Ishizaki, Yoshito; Torisu, Hiroyuki; Saitsu, Hirotomo; et al.
Summary: Advance in the exome‐wide sequencing analysis contributes to identifying hundreds of genes that are associated with early‐onset epileptic encephalopathy and neurodevelopmental disorders. On the basis of massive sequencing data, functional interactions among different genes are suggested to explain the common molecular pathway underlying the pathogenic process of these disorders. However, the relevance of such interactions with the phenotypic severity or variety in an affected individual remains elusive. In this report, we present a 45‐year‐old woman with neurofibromatosis type 1 (NF1), infantile‐onset epileptic encephalopathy, and severe developmental delay. Whole‐exome sequencing identified de novo pathogenic mutations in NF1 and the Schaaf‐Yang syndrome‐associated gene, MAGEL2 . Literature‐curated interaction data predicted that NF1 and MAGEL2 proteins were closely connected in this network via their common interacting proteins. Direct conversion of fibroblasts into neurons in vitro showed that neuronal cells from 9 patients with NF1 expressed significantly lower levels of MAGEL2 (54%, p = 0.0047) than those from healthy individuals. These data provide the first evidence that pathogenic mutations of NF1 deregulate the expression of other neurodevelopmental disease‐associated genes. De novo mutations in multiple genes may lead to severe developmental phenotypes through their cumulative effects or synergistic interactions.